Strategi Penataan Kawasan Tepian Sungai Kapuas di Kelurahan Benua Melayu Laut - Muhammad Mahfud; Ernady Syaodih (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The changed-functioning riverside areas are characterized by the presence of different types of buildings that are not well organized, both physically and functionally. One of the river areas of interest is the Kapuas Riverside in Pontianak, which has become an icon and attraction to visitors. This research was conducted on the riverbanks of Benua Melayu Laut Urban Village, South Pontianak District, Pontianak City, West Kalimantan. This area became a built-up area (people's homes). One of the arrangements that are being carried out by the Pontianak city government is to construct a waterfront on the banks of the Kapuas river. This development is carried out as a new city program, in the Pontianak City Regional Spatial Plan (RTRW) for 2013-2033. The approach method used in this study is a quantitative descriptive approach and SWOT analysis. This analysis was carried out to develop a strategy for structuring the Kapuas riverbank area in the Benua Melayu Laut Urban Village. Based on the analysis that has been done, there are several strategies for structuring the banks of the Kapuas river using 8 elements of Hamid Shirvani's arrangement as well as social and economic aspects in the research area. One of the structuring strategies that have to be followed up by relevant stakeholders in the construction of street vendor stalls by the Department of Cooperatives and small and medium enterprises in order for the activities can continue and pedestrian circulation is not disrupted. The results of the study showed an aggressive strategy by optimizing the opportunities that exist in the arrangement effort. So the proper technique was to make internal improvements and actively develop existing opportunities so as to create better conditions). Abstrak. Wilayah Tepian Sungai yang sudah mengalami alih fungsi ditandai dengan adanya berbagai macam bangunan yang tidak tertata baik fisik maupun fungsinya. Salah satu kawasan tepian sungai yang menjadi perhatian adalah tepian Sungai Kapuas di Kota Pontianak yang menjadi ikon serta menjadi daya tarik pengunjung. Penelitian ini dilakukan di Tepian Sungai Kapuas di Kelurahan Benua Melayu Laut, Kecamatan Pontianak Selatan, Kota Pontianak, Kalimantan Barat. Wilayah ini menjadi kawasan terbangun (rumah tinggal warga). Salah satu penataan yang sedang dilakukan oleh pemerintah Kota Pontianak adalah dengan membangun waterfront di tepian Sungai Kapuas. Pembangunan ini dilakukan merupakan program Kota baru, pada Rencana Tata Ruang Wilayah (RTRW) Kota Pontianak tahun 2013-2033. Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif dan analisis SWOT. Analisis ini dilakukan untuk menyusun strategi penataan Kawasan tepian Sungai Kapuas di Kelurahan Benua Melayu Laut. Berdasarkan analisis yang telah dilakukan ada beberapa Strategi Penataan Kawasan Tepian Sungai Kapuas dengan menggunakan 8 elemen penataan Hamid Shirvani serta aspek sosial dan ekonomi di wilayah penelitian. Salah satu strategi penataan yang perlu ditindaklanjuti oleh stake holder terkait adalah pembangunan kios-kios PKL oleh Dinas Koperasi dan UMKM agar akivitas ekonomi masyarakat tetap berjalan serta sirkulasi pejalan kaki tidak terganggu. Hasil penelitian menunjukan agresif strategy dengan mengoptimalkan peluang yang ada dalam upaya penataan. Maka startegi yang tepat adalah melakukan perbaikan internal dan secara aktif mengembangkan peluang yang ada sehingga dapat menciptakan kondisi yang lebih baik.